Feminism in Yellowface - Chang, Stewart (2015)
This article analyzes the relationship between sexualized stereotypes of Asian women, specifically the Asian prostitute epitomized in the Suzie Wong stereotype, and the tendency of American immigration law, even in pro-women legislation such as the TVPA, to promote conservative norms regarding female sexuality and domesticity. Part I explains the significance of Asian prostitution in the history and evolution of United States immigration policy. In the nineteenth century, the Asian prostitute was constructed as the antithesis to normative American sexuality, as a foreign peril that threatened the integrity of the American domestic unity and therefore required rejection and exclusion. Part II traces how the stereotype of the Asian prostitute evolved during the twentieth century to be reconfigured in the American legal imagination as the unwitting sex trafficking victim who is no longer threatening to the American family unit, but is capable of finding refuge and redemption through normative American domesticity. Part III analyzes the ways in which the TVPA, through a system of compulsory confession under the T-visa regulations, requires female applicants to see themselves as victims, reinforcing conservative norms and traditions regarding immigrant female sexuality. The confession also functions as a cultural repudiation, which further ensconces a moral hierarchy of Western above Eastern cultural values surrounding sexuality. Part IV considers how the selection and legitimization of immigrant subjects who demonstrate normative sexuality, even in facially benevolent legislation such as the TVPA, nevertheless perpetuate stereotypes that are damaging not only to minority immigrant communities but also to women generally. The stereotyping of Asian women as sexual model minorities like Suzie Wong legitimizes laws that continue to exclude aliens deemed to possess illegitimate sexualities, which more broadly perpetuates cultural and legal assumptions regarding the proper conduct of women